Correction: Rashba exciton in a 2D perovskite quantum dot. Issue 46 (25th November 2021) - Swift, Michael W.; Lyons, John L.; Efros, Alexander L.; Sercel, Peter C.
Abstract : Correction for 'Rashba exciton in a 2D perovskite quantum dot' by Michael W. Swift et al., Nanoscale, 2021, 13, 16769–16780, DOI: ; 10.1039/D1NR04884H .